L’offre de travail dans le modèle CANDIDE : un commentaire - Fortin, Bernard; Gautrin, Jean-François (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractThe paper is a brief critical evaluation of the treatment of the "supply of labour" in the CANDIDE model. The authors note that the "supply of labour block" does not occur to have retained much of the effort of the CANDIDE developing team. With regards to the specification of the equation of supply of labour, no attempts have been made to integrate new developments in labour economics (a better treatment of the secondary workers supply of labour, a Fisherian utility maximising approach). We note certain econometric difficulties which have not been overcome: The limited dependant variable problem, the lag structure problem…Finally, though it is encouraging to see attempts in macro-economic models to integrate explicitly a labour demand and supply block with a certain disagregation, important economic problems in the labour market can be dealt only with much more flexible and disagregated models than CANDIDE.